Utilization Of Instagram For The Dissemination Of Lupus Information: An Analysis Of The Four Pillars Of Social Media Strategy - Mochammad Arifin Nafi; Lukman Hakim (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
Systemic Lupus Erythematosus (SLE) is a chronic disease that still faces challenges in terms of health literacy, social stigma, and limited support for its sufferers. In this context, social media is a strategic medium for healthcare organizations to convey information, build audience engagement, and facilitate community support. This study aims to analyze the digital health communication strategy of the Lupus Indonesia Foundation through the @yayasanlupusindonesia Instagram account using the framework of the Four Pillars of Social Media Strategy of Safko and Brake. This study uses a descriptive qualitative approach with the support of quantitative content analysis. The research data included 49 purposively selected Instagram posts, as well as audience comments collected through a scraping process using Apify's tools. The analysis is focused on the implementation of content strategies, audience engagement patterns, and user responses and sentiment. The results of the study show that the communication strategy of the Indonesian Lupus Foundation is not only oriented towards the delivery of health information, but also emphasizes a dialogical, collaborative, and empathetic approach. Communication and education-based content shows a relatively higher level of audience engagement, while the comment column serves as a digital social support space for people with lupus. These findings indicate that effective digital health communication in the context of chronic disease needs to integrate informational, relational, and affective dimensions simultaneously. This research provides a theoretical contribution in strengthening the relevance of the Four Pillars of Social Media Strategy in the study of digital health communication, as well as a practical contribution for health organizations in designing more participatory and sustainable social media communication strategies.